Pendidikan politik perempuan dalam menghadapi pemilihan kepala daerah Provinsi Jambi tahun 2020 - Sutri Destemi; Hartati Hartati (Unri Conference Series: Community Engagement, 2020)
We continue to pursue various breakthroughs through affirmative policies and strengthening the role of women in politics. One of these efforts can be seen through the application of the Election Law which requires the involvement of women at least 30 percent as legislative candidates for political parties. This policy is explicitly translated by the General Election Commission (KPU) in KPU regulation Number 7/2013 which states that political parties that cannot meet these requirements cannot qualify as election participants. However, at the implementation stage the level of women's participation in politics is still low. Political parties have not been able to produce reliable female cadres. The basic assumption behind this is that political education for women in Indonesia is not sufficient to open political awareness. The method used in this service is community empowerment through political education for women's groups / organizations / communities in Pijoan Village. The function of political education is not only the role of Political Parties but also transfers to all levels of society, especially the educational environment and academics. Therefore, this service is expected to be able to increase public awareness, especially women, to actively participate in the upcoming regional head elections for Jambi province. Based on the results of the survey carried out after the service, the participants received motivation to be more active in various activities such as organizations and in government and political activities.